2010
DOI: 10.1179/174328409x441229
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanodispersions on strength–ductility properties of semisolid cast A356 Al alloy

Abstract: The present investigation studies the prospects of using nanoparticles as reinforcement agents to gain improved performance of A356 Al cast alloy by adding up to 5% Al2O3 and TiO2 particles. The particles size was intentionally reduced from 10 μm to 500 nm to 40 nm. To evaluate the results, the alloys were further characterised by various metallurgical and mechanical characterisation methods. The results showed that introducing nanoparticles into semisolid slurries has a beneficial effect on optimising strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…Prospects of using nanoparticles as refining and reinforcement agents to gain improved performance of Al-Si cast alloys by adding Al2O3 and TiO2 particles have gained significant interest recently [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospects of using nanoparticles as refining and reinforcement agents to gain improved performance of Al-Si cast alloys by adding Al2O3 and TiO2 particles have gained significant interest recently [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that enhanced as-cast properties of Al-Si alloys are obtained by treating the melt with nano-sized particles [16][17][18][19][20][21][22]. Introducing Al2O3 nanoparticles to the (A356) cast alloy in the semi-solid state with mechanical stirring has a beneficial effect on improving the strength-ductility relationship in these alloys [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…5, showing that the ED process for copper on large alumina particles can be difficult. Our previous study [19] indicated that the quality of copper coating on larger micron sized particles is not as good as on smaller particles. It was reported previously that the deposition time for smaller particles was higher than that for larger particles, indicating that finer particles have more time to be exposed to the deposition process [20].…”
Section: Resultsmentioning
confidence: 95%
“…Stir casting in the semi-solid state is the most frequently used method for production of particulate AMMCs [9][10][11][12][13][14][15][16][17][18][19]. Coating or oxidizing the reinforcement particles, adding some surface-active elements such as magnesium into the matrix, and stirring of metal matrix alloy for an adequate time period during incorporation are some ways used in the semi-solid stir casting process to aid particle incorporation and chemical bonding with the matrix [5,7,13,[20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation [15] studies the prospects of using nanoparticles as reinforcement agents to gain improved performance of A356 Al cast alloy by adding up to 5 % Al 2 O 3 and TiO 2 particles. The particles size was intentionally reduced from 10 mm to 500 nm and to 40 nm.…”
Section: Mmcs Production Technologiesmentioning
confidence: 99%